2010
DOI: 10.1007/s12288-010-0047-x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Trends in Transfusion Transmitted Infections Among Blood Donors in a University Hospital Blood Bank: A 5 Year Study

Abstract: Blood is life. Transfusion of blood and blood components, as a specialized modality of patient management saves millions of lives worldwide each year and reduce morbidity. It is well known that blood transfusion is associated with a large number of complications, some are only trivial and others are potentially life threatening, demanding for meticulous pretransfusion testing and screening particularly for transfusion transmissible infections (TTI). These TTI are a threat to blood safety. The priority objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
87
12
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 9 publications
39
87
12
4
Order By: Relevance
“…Dominancy of male blood donors were also found in a study conducted in North India, which was in accordance with our study [20]. There are some other reports supported this outcome [19][20][21][22][23]. There could be another possibility that, females due to their poor nutritional status may be anemic, so they were unwilling to donate blood.…”
Section: Gender and Age Distribution Of The Participantssupporting
confidence: 91%
“…Dominancy of male blood donors were also found in a study conducted in North India, which was in accordance with our study [20]. There are some other reports supported this outcome [19][20][21][22][23]. There could be another possibility that, females due to their poor nutritional status may be anemic, so they were unwilling to donate blood.…”
Section: Gender and Age Distribution Of The Participantssupporting
confidence: 91%
“…But Pallavi et al observed in their study a much higher prevalence of 0.28% with respect to syphilis [11]. In the recent years syphilis has also acquired a new potential for morbidity and mortality through association with increased risk of HIV infection, thus making safe blood more difficult to get.…”
Section: Discussionmentioning
confidence: 85%
“…Seropositivity of VDRL infection has been constant (0.01%) in the last 12 years from 2001 -2012. The data which provides a picture of TTI burden in India has come from various seroprevalence studies (Table 4 and Table 5 [19]. The Indian National AIDS Control Organization (NACO) suggested an overall prevalence of 0.91% (2005) in India with 0.25% in Delhi [21].…”
Section: Discussionmentioning
confidence: 99%